Rezydencja duchownych w dyspozycjach Kodeksu Prawa Kanonicznego z 1983 r. - Adamczyk, Jerzy (Prawo Kanoniczne, 2005)
The canonical adagium: „Bonum animarum suprema lex” - is expressed distinctively m the issues of residence sketched in the Code. The residence is an obligation of ermanent staying in the place of performing of the ministry. The Church always emphasised the necessity of residence. The notion of residence as it is stated in the Code of John Paul II was showed m the first part of this article. Then, the problems concerning persons having the obligation of esidence were considered. At last we discussed the question of neglecting of esidence. It seems that presented regulations relevant to necessity of residence of clergymen should help to exhibit the care of Church for salvation of souls more competently and fully.